2021
DOI: 10.1101/2021.02.17.21251928
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mortality after surgery with SARS-CoV-2 infection in England: A population-wide epidemiological study

Abstract: Objectives: To confirm the incidence of perioperative SARS-CoV-2 infection and associated mortality after surgery. Design and setting: Analysis of routine electronic health record data from National Health Service (NHS) hospitals in England. Methods: We extracted data from Hospital Episode Statistics in England describing adult patients undergoing surgery between 1st January 2020 and 31st October 2020. The exposure was SARS-CoV-2 infection defined by ICD-10 codes. The primary outcome measure was 90-day in-h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…This led to the almost complete cessation of all but the most emergent surgical treatment. The reintroduction of surgery after the first wave of the pandemic was complicated by several factors: first, concerns about the high risk of perioperative mortality amongst surgical patients with concomitant COVID-19 and the postponement of surgery on clinical grounds 18 , 20 ; second, reduced availability of physical and human resources as a result of ongoing care of patients with COVID-19, which limited the capacity of surgical services 21 ; and third, reduced throughput of surgery as a result of new infection control procedures to prevent nosocomial infection and to protect staff members. The consequences of the observed interruption to surgical treatment will be felt by millions of patients for many years to come.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This led to the almost complete cessation of all but the most emergent surgical treatment. The reintroduction of surgery after the first wave of the pandemic was complicated by several factors: first, concerns about the high risk of perioperative mortality amongst surgical patients with concomitant COVID-19 and the postponement of surgery on clinical grounds 18 , 20 ; second, reduced availability of physical and human resources as a result of ongoing care of patients with COVID-19, which limited the capacity of surgical services 21 ; and third, reduced throughput of surgery as a result of new infection control procedures to prevent nosocomial infection and to protect staff members. The consequences of the observed interruption to surgical treatment will be felt by millions of patients for many years to come.…”
Section: Discussionmentioning
confidence: 99%
“… 25 We have previously demonstrated that ‘green pathway’ operating (in which elective patients are preoperatively screened for COVID-19, isolated in the preoperative period, and kept separate from acute admissions) is safe, with similar perioperative mortality amongst patients on green pathways compared with before the pandemic. 20 Consequently, surgery should not be delayed or prevented if safeguards are put in place. However, this will require significant reorganisation of surgical services and financial commitment from central government.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown worse postoperative outcomes in individual patients with COVID-19 infection 5,6 , even in settings with low overall incidence of perioperative COVID-19 infection 7,8 .…”
mentioning
confidence: 94%
“…Editor – Recent data suggest that patients with SARS-CoV-2 infection carry a higher risk of postoperative respiratory complications and mortality within 7 weeks of diagnosis, 1 , 2 such that the thresholds for surgery during the COVID-19 pandemic should be higher than during normal practice. 3 The American Society of Anesthesiologists (ASA) recommends that elective surgery be delayed for four weeks even in asymptomatic patients testing positive for SARS-CoV-2.…”
mentioning
confidence: 99%